The influence of people management practices on a culture of lean manufacturing - Trentin, Luciano Masculino; Tontini, Gérson (Revista de Administração da UFSM, 2022)
Purpose – This article aims to assess the perception of the influence of people management practices on the process of implementing a lean manufacturing culture. Design/methodology/approach – The sample consisted of 303 respondents from five textile companies located in the southern region of Brazil, being collected by accessibility and convenience. Multiple regression analysis was used for data treatment and analysis. Findings – As a result, the research showed that people management practices (recruitment and selection, retaining talent, people development, and work environment) influence the implementation of lean manufacturing in organizations. In contrast, the working contract practice did not show an influence on the implementation of lean manufacturing. Research limitations/implications – The use of a certain market segment considering a cross-sectional view can be considered a limitation of the study, therefore, the data may not express the results that would be obtained if analyzed in different market segments. Practical implications – Pragmatically, it can be considered that this research contributes so that the main organizational managers can choose the most appropriate people management practice during the process of implementing a lean manufacturing culture, that is, investing essentially in retention and employee training. Originality/value – This study is relevant and contributes to the expansion of scientific studies about people management practices and the implementation of lean manufacturing. In addition, the study allows managers of textile organizations to understand the level of implementation of lean manufacturing, and which people management practices should be prioritized in the adoption of lean.